Loving Kindness Meditation: An Intervention to Increase Positivity Following Interpersonal Transgressions - Halverson, Kjerstin; Ellen Petersen (Forum Pedagogiczne, 2024)
Objective- To determine if a single 15-minute guided LKM intervention can increase an individual’s feelings of forgiveness toward someone who has caused them harm. Methods- Participants (N = 49; mean age = 18-21 years) were asked to recollect and describe an incident where another individual hurt them then randomized to either a control, secular LKM, or spiritual LKM. Baseline measurements included demographics, emotional forgiveness scale (EFS), attitudes related to spirituality (ARES), anxiety and depression (PHQ-4), positive and negative affect (PANAS), single stress item (SSI), self-critical rumination scale, gratitude (GQ-6), and Batson empathy scale. All measures, excluding demographics and ARES, were assessed post-intervention. Results- No significant differences were identified between groups for all measures except positive affect as measured by PANAS and gratitude as measured by GQ-6. These results remained significant even when covarying for baseline spiritual beliefs. Conclusions- Our single 15-minute intervention was successful in increasing gratitude for participants in the spiritual intervention group when compared to the control and borderline significance comparing the control and the secular intervention.